Harmonic Bridges: Enhancing Social Functioning in Children with Autism through Musical Scaffolding - Prof. Mamta Sharma; Aashita Mehta (International Journal of Indian Psychȯlogy, 2025)
This study investigates the effectiveness of Musical Scaffolding in enhancing Social Functioning in children with Autism Spectrum Disorder (ASD). Social Functioning, a core human skill involving meeting & greeting, empathy etc., can be targeted through Music-based interventions. It was hypothesized that Musical Scaffolding would improve overall SF, particularly in sub-domains like Communication & Cognition, Emotional Control, within the experimental group as compared to the control group. A pre-post assessment design was employed, involving N=100 children (already diagnosed) with ASD. Divided equally, 50 children participated in the experimental group receiving bi-weekly 40-minute MT sessions for eight weeks. Music therapy incorporated rhythm and melody/swar-based activities. Tool used to measure SF is Social Responsiveness Scale, 2nd edition (SRS-2; Constantino & Gruber, 2012). Results demonstrated significant improvement in the experimental group’s SF, with better post-intervention scores indicating reduced dysfunctionality. Statistical analysis revealed a significant difference in EF between the control and experimental groups.